A Nationwide pilot project to develop rehabilitation services for patients with cardiovascular diseases - Marina Bubnova; David Aronov; Olga Barbarash; Nadezhda Lyamina; Svetlana Pomeshkina; Galina Chumakova (Medical Journals Sweden, 2021)
Objective: To measure progress towards introducing a 3-phase rehabilitation programme, based on the multidisciplinary approach, for patients with cardiovascular diseases. Methods: Seventeen hospital and outpatient medical centres from 13 regions of the Pilot Project. Baseline questionnaires assessed the involvement of multidisciplinary teams, staffing, and the equipment in healthcare facilities. These questionnaires covered 3 rehabilitation phases: inpatient rehabilitation in the intensive care units and departments of myocardial infarction/cardiac surgery; early in-hospital rehabilitation; and outpatient rehabilitation. Results: The pilot project was initiated in 2013. At the 5-year follow-up, phase I was established across all 17 sites, phase II at 13 sites, and phase III at 9 sites. By 2017, multidisciplinary teams were deployed to manage patients at all sites. Early rehabilitation in regional vascular centres, reduced patients' stay from 13.7 (2.1) days in 2013 to 7.6 (1.1) days in 2017. Conclusion: Despite successful implementation of the 3-phase rehabilitation programme based on the multidisciplinary approach, further improvement is required, with the main focus shifted to patients routing between healthcare facilities. Particular attention should be paid to the standards for providing phase III cardiac rehabilitation, in order to ensure continuity of cardiac rehabilitation. The next step should include assessment of the effectiveness of the implemented cardiac rehabilitation programme and its translation to other regions of the country.